Differences in the Levels of Interleukin-1Î² (IL-1Î²) and Interleukin-1 Receptor Antagonist (IL-1ra) in Children with Status Epilepticus and Febrile Seizure - Shofiyah, Fita; Muid, Masdar; Sujuti, Hidayat (Journal of Tropical Life Science, 2017)
Proinflammatory cytokines are elevated in status epilepticus and febrile seizure and associated with tissue damage. This study aimed to investigate the differences in interleukin 1 beta (IL-1Î²) and interleukin 1 receptor agonist (IL-1ra) levels in status epilepticus as compared with febrile seizure and febrile. This cross-sectional study was designed to include 45 subjects divided equally into three groups (status epilepticus, febrile seizure, and febrile). Both IL-1Î² and IL-1ra were measured by using an ELISA method. Results showed that IL-1Î² levels were significantly higher in the status epilepticus group as compared with the febrile seizure and febrile groups (p < 0.05). IL-1ra levels in the status epilepticus group were significantly lower compared with the febrile seizure group (p = 0.04). Consistently, the IL-1Î²/IL-1ra ratio in the status epilepticus group was significantly higher as compared with the febrile seizure group (p = 0.01). We concluded that IL-1Î² and the IL-1Î²/IL-1ra ratio were significantly higher in status epilepticus. IL-1ra levels were significantly higher in the febrile seizure group.